2006
DOI: 10.1002/ardp.200500216
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Triterpenes and Flavonoids on the Enzymatic Activity of Hyaluronic Acid‐Splitting Enzymes

Abstract: The effect of triterpenes and flavonoids on the activity of several hyaluronic acid-splitting enzymes was investigated. Studies showed that the inhibitory effect of the triterpenes glycyrrhizin and glycyrrhetinic acid is dependent on the source of hyaluronate lyase. Hyaluronate lyase from Streptococcus agalactiae (Hyal B) and recombinant hyaluronate lyase from Streptococcus agalactiae (rHyal B) demonstrated strongest inhibition. In contrast, hyaluronate lyases from Streptomyces hyalurolyticus (Hyal S), Strepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 28 publications
2
22
0
2
Order By: Relevance
“…In agreement with our study, previous in vitro research reported that 30 different flavonoid components exhibited inhibition against BTHase, and that inhibition levels were determined, from highest to lowest, in silibinin4kaempferol4apigenin4luteolin4tan-nin 33 . The idea that flavonoids possess anti-hyaluronidase activity has also been supported by other studies 4,8,12,34 .…”
Section: Resultsmentioning
confidence: 53%
“…In agreement with our study, previous in vitro research reported that 30 different flavonoid components exhibited inhibition against BTHase, and that inhibition levels were determined, from highest to lowest, in silibinin4kaempferol4apigenin4luteolin4tan-nin 33 . The idea that flavonoids possess anti-hyaluronidase activity has also been supported by other studies 4,8,12,34 .…”
Section: Resultsmentioning
confidence: 53%
“…17,31) Lithospermic acid B is a phenylpropanoid tetramer with inhibitory activity comparable to that of the oligomers. Some flavonoids have been reported to inhibit of hyaluronidase, 32,33) and diosmetin-7-O-b-D-glucuronide and apigenin-7-O-b-Dglucuronide were also revealed as active compounds. Previously, in phytochemical studies of the Meehania genus, we found 23 spermidine alkaloidal glycosides in M. urticifolia.…”
Section: -21)mentioning
confidence: 99%
“…Further, glycyrrhizin and glycyrhetinic acid showed maximum inhibition towards Hyal B (Streptococcus agalactiae) and rHyal B (recombinant S. agalactiae), whereas, the weak inhibition was observed for HAase from the bovine testis, Hyal S (Streptomyces hyalurolyticus), and Hyal C (S. equisimilis). A noncompetitive dead end inhibition was observed for glycyrrhizin on rHyal B [145]. In the same study, the authors selected different flavonoids depending on their number of hydroxyl groups and side chain substituents.…”
Section: Flavonoids and Terpenesmentioning
confidence: 99%